A patient with COVID-19 and bleeding complications due to neurofibromatosis type 1 during VV-ECMO: A case report. Issue 51 (23rd December 2021) - Shimoyama, Keiichiro; Azuma, Kazunari; Oda, Jun
Abstract: Rationale: The many deaths from coronavirus disease (COVID-19) since 2019 have caused global concern. Effective treatment has not yet been established; supportive care is the main treatment. It has been suggested that veno-venous extracorporeal membrane oxygenation (VV-ECMO) may be effective in severe cases that do not respond to ventilator management. Patient concerns and diagnosis: We report the case of a 68-year-old woman with severe respiratory failure due to COVID-19 who was treated with VV-ECMO but suffered from bleeding complications. She presented with multiple café-au-lait lesions and neurofibromas on her skin and was diagnosed pathologically as having neurofibromatosis type 1(NF1). Interventions and outcomes: Although she received appropriate anticoagulation therapy with heparin at the initiation of VV-ECMO, she had 5 episodes of severe bleeding, each requiring transcatheter arterial embolization and massive transfusion. In patients with NF1, vascular fragility has been noted due to vascular infiltration of neurofibromas and degeneration of vascular structures. Therefore, the causes of frequent bleeding complications may be related to the fragility of blood vessels in patients with NF1. VV-ECMO in patients with NF1 is likely to result in frequent bleeding complications and the need for massive transfusion. Lesson: We propose non-anticoagulation treatment strategy for the management of VV-ECMO in patients with NF1. Especially under the COVID-19 pandemic, more careful consideration should be given to the indications for VV-ECMO in patients with NF1.